2022
DOI: 10.1186/s13059-021-02585-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics analysis identifies T and NK cell activation as a driver of epigenetic clock progression

Abstract: Background Epigenetic clocks use DNA methylation (DNAm) levels of specific sets of CpG dinucleotides to accurately predict individual chronological age. A popular application of these clocks is to explore whether the deviation of predicted age from chronological age is associated with disease phenotypes, where this deviation is interpreted as a potential biomarker of biological age. This wide application, however, contrasts with the limited insight in the processes that may drive the running of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 74 publications
9
35
0
Order By: Relevance
“…However, we still lack sufficient evidence to confidently compare the biological ages between samples from different tissues. For example, as recently reported by Jonkman and colleagues, the Horvath’s multi-tissue clock predicts naive T cells to be up to 30 years younger than activated T cells from the same donor [41]. Can we conclude the naive T cells are biologically 30 years younger than activated T cells?…”
Section: Discussionmentioning
confidence: 72%
“…However, we still lack sufficient evidence to confidently compare the biological ages between samples from different tissues. For example, as recently reported by Jonkman and colleagues, the Horvath’s multi-tissue clock predicts naive T cells to be up to 30 years younger than activated T cells from the same donor [41]. Can we conclude the naive T cells are biologically 30 years younger than activated T cells?…”
Section: Discussionmentioning
confidence: 72%
“…A few studies support that notion. Peripheral blood cell profiling of six cohorts spanning a wide range of chronological age and pathological conditions, revealed that a minority of Horvath clock CpG correlate with expression of genes in cis that are not significantly enriched in any Gene Ontology term [ 21 ]. Epigenetic ageing was weakly associated with classical cardiovascular risk factors in the large MESA and HRS cohorts [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the latter two studies agree with our observation that epigenetic ageing was not associated with asymptomatic/symptomatic status in the carotid atheroma. As caveat , Horvath clock CpG are associated with gene expression in trans in loci that regulate T cell function and may therefore be relevant for atherosclerosis [ 21 , 24 , 25 ]. As the atheroma discontinuously expands by bursts in macrophage infiltration and cellular proliferation, it is possible that the epigenetic clock is a readout of mitotic age in atherosclerosis [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have begun to elucidate the biological processes that explain age acceleration associations detected using epigenetic clocks [40]. In a functional genomics study, changes in proportions of naive and activated immune blood cells were strongly associated with the Hannum and Horvath age acceleration measures [40].…”
Section: Discussionmentioning
confidence: 99%